Semibatch emulsion copolymerization in the presence of n-methylol acrylamide: effects of emulsifier type and concentration - Kahraman, Ayca; Sarac, Ayfer (WILEY, 2009)
Two types of emulsifier were studied to compare the colloidal and physicochemical properties of vinyl acetate (VAc)/(BuA) emulsions. Emulsions were prepared by varying the composition and the concentration of the anionic and nonionic emulsifiers. An increase in the total emulsifier concentration of anionic and nonionic emulsifier percentage leads to dispersions with smaller particles and higher viscosities. Using anionic and nonionic emulsifiers in copolymer latexes, it was observed that the viscosity goes through a maximum which is located at total emulsifier concentration of about 3.6wt% The surface tension of the copolymers shows a drastic increase at a concentration above 3.5% for mixed emulsifier systems. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: copolymerization; lattice; surfactant; viscosity; surface tension; Polymer Science